Analisis Kinerja Keuangan Pada Subsektor Pariwisata Yang Terdaftar Pada Bursa Efek Indonesia - Hasucita Tausi; Hamdy Hady; Febria Nalurita (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of quick ratio variables, total asset turnover ratio, leverage, firm size and growth in sales on financial performance as measured by Return on Equity (ROE). The data in this study uses secondary data sourced from the annual financial statements of tourism subsector companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The sample selection was carried out by purposive sampling so that 17 companies were sampled. The dependent variables in this study are the quick ratio, total asset turnover ratio, leverage, firm size and growth rate. The data analysis used to test the hypothesis is multiple regression analysis using the Eviews 10 program. The results show that the quick ratio and growth have no effect on financial performance, while those that do affect the total asset turnover ratio, leverage, and firm size. To increase profits through the total asset turnover ratio, one way that can be done is that asset management is carried out wisely. Leverage is one of the challenges for managers in terms of company management. If the company expands the size of the company, it will allow the advancement of competitive advantage and dominate market share. The results of this study are expected to provide input for companies and investors to consider the total asset turnover ratio, leverage, and company size because they will affect the company's financial performance.